2022
DOI: 10.1002/jhm.12847
|View full text |Cite
|
Sign up to set email alerts
|

Associations between hospitalist physician workload, length of stay, and return to the hospital

Abstract: Background: Hospitalist physicians' workload-the total number of patients they care for daily-is rising in the U.S. Hospitalists report that increased workload negatively affects patients care.Objective: Measure the associations between hospitalist physicians' workload and clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Elliot et al 3 reported that, based on the census and RVUs, the increase in hospitalists’ workload is associated with the increase in length of stay and hospital costs. Djulbegovic et al 9 affirmed that the length of stay was prolonged by 0.05 days when comparing the 75th workload percentile with the 25th workload percentile (95% CI, 0.02–0.08; P < 0.001). Moreover, Guan et al 10 found that higher rates of inappropriate prescribing were associated with heavier workloads ( β = 0.132, SE = 0.016; P < 0.001), whereas Wingo et al 11 reported that an increase in the attending physician’s workload was associated with an increase in patient safety indicators such as transfers to the intensive care unit, calls to the rapid response team, and deaths (OR, 1.81; 95% CI, 1.21–2.71; P = 0.0001).…”
Section: Discussionmentioning
confidence: 99%
“…Elliot et al 3 reported that, based on the census and RVUs, the increase in hospitalists’ workload is associated with the increase in length of stay and hospital costs. Djulbegovic et al 9 affirmed that the length of stay was prolonged by 0.05 days when comparing the 75th workload percentile with the 25th workload percentile (95% CI, 0.02–0.08; P < 0.001). Moreover, Guan et al 10 found that higher rates of inappropriate prescribing were associated with heavier workloads ( β = 0.132, SE = 0.016; P < 0.001), whereas Wingo et al 11 reported that an increase in the attending physician’s workload was associated with an increase in patient safety indicators such as transfers to the intensive care unit, calls to the rapid response team, and deaths (OR, 1.81; 95% CI, 1.21–2.71; P = 0.0001).…”
Section: Discussionmentioning
confidence: 99%
“…1 Measuring the ADC at midnight may underestimate the work required of clinical teams during times of peak census, which also represents peak admission and discharge times. Understaffing during peak hours may contribute to decreased throughput 9 and increased levels of physician burnout. 10 If census is being measured at just one time of day, our data suggest that hospitals should consider doing so at the time of peak census, which at our institution occurred between 7 a.m. and 11 a.m.…”
Section: Discharges Occurred Almost Exclusively During Daytime Hoursmentioning
confidence: 99%
“…Full-capacity protocol is a host of actions that can include transferring ED patients to the "next-appropriate" bed (e.g., inpatient hallways, dialysis rooms), 37,38 and is associated with lower quality, [39][40][41] perhaps through the influence on workload. Higher workload for inpatient physicians and nurses is associated with increased length of stay, 42,43 higher readmissions, 44,45 and higher mortality and morbidity. 43,[46][47][48] This may occur because higher workload may challenge efficiency and stretch physician and staff capacity and time with each patient, leading to a longer length of stay and higher risk of mortality.…”
Section: Introductionmentioning
confidence: 99%